2001
DOI: 10.21273/hortsci.36.7.1318
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Markers Associated with Morphological Traits in Watermelon

Abstract: Morphological traits were examined in an F3 generation derived from a cross between C. lanatus var. lanatus [(Thunb.) Matsum. & Nakai] and C. lanatus var. citroides. At least three genes, C (yellow) vs. c (red), i (inhibitory to C) vs. I (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
12
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 26 publications
0
12
0
Order By: Relevance
“…Tomato seed are approximately the same size as tomato seed, whereas tiny seed size is smaller than 5 mm but larger than tomato seed size (Gusmini, 2005;Wehner et al, 2001). High correlations (r = 0.9) among seed weight, seed length, and seed width have been reported (Hawkins et al, 2001;Poole et al, 1941;Zhang et al, 1995), suggesting a pleiotropic effect and leading to seed size usually being described in terms of seed length . Poole et al (1941) suggested that two genes, l and s, control seed length for large, medium, and small seed sizes with mediumsized seed being dominant and s epistatic to l. The suggested genotypes for long, medium, and short seeds are llS-, L-S-, and -ss, respectively (Poole et al, 1941).…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…Tomato seed are approximately the same size as tomato seed, whereas tiny seed size is smaller than 5 mm but larger than tomato seed size (Gusmini, 2005;Wehner et al, 2001). High correlations (r = 0.9) among seed weight, seed length, and seed width have been reported (Hawkins et al, 2001;Poole et al, 1941;Zhang et al, 1995), suggesting a pleiotropic effect and leading to seed size usually being described in terms of seed length . Poole et al (1941) suggested that two genes, l and s, control seed length for large, medium, and small seed sizes with mediumsized seed being dominant and s epistatic to l. The suggested genotypes for long, medium, and short seeds are llS-, L-S-, and -ss, respectively (Poole et al, 1941).…”
mentioning
confidence: 98%
“…Watermelon seed size has traditionally been divided into qualitative categories as being large, medium, small, tomato, or tiny (Hawkins et al, 2001;Poole et al, 1941;Zhang, 1996b). Poole et al (1941) defined large, medium, and small seed as having average seed lengths of 13, 10, and 6 mm, respectively.…”
mentioning
confidence: 99%
“…. Epistatic interactions among flavonoid genes are common (Conner and Erickson, 1991;Fick, 1976;Hawkins and Dane, 2001;Pahlavani et al, 2004;Tyrach and Horn, 1997) because several key enzymes in the flavonoid biosynthetic pathway have multiple precursors.…”
mentioning
confidence: 99%
“…The interaction of these genes produced six base colors: black (RR TT WW); clump (RR TT ww); tan (RR tt WW); white with tan tip (RR tt ww); red (rr tt WW); and white with pink tip (rr tt ww) (Kanda, 1931;McKay, 1936;Poole, 1941). Furthermore, a modified gene, d was proposed to be responsible for a black dotted seed coat (Poole, 1941;Hawkins et al, 2001). A single pair of gene, c r was reported to account for the formation of the cracks on the seed coat (Abd el-Hafez et al, 1985).…”
Section: Discussionmentioning
confidence: 99%